سوء التغذية الشديد عند الاطفال - زعبلاوي, يوسف; زاهر, محمد; عباس, نتاشا (Latakia University Journal -Medical Sciences Series, 2019)
شملت دراستنا التي أجريت في مشفى الأسد الجامعي في اللاذقية في الفترة بين( 10/2002 و10/2003) 23 طفلا كان لديهم سوء تغذية شديد وفق مشعر Z-score المعتمد عالميا وقبل هؤلاء الأطفال في المشفى لأسباب مختلفة, وقد توزعوا: 15 طفلا مصابا بالسغل, 7 أطفال مصابين بالكواشيركور سغلي, وطفل واحد مصاب بالكواشيركور. تراوحت أعماره بين 40 يوم وسنتين, وكان منهم 15 ذكر و8 إناث . ولقد وجدنا في دراستنا أن الفقر والجهل بقواعد التغذية الصحيحة عند الأطفال والمستوى الثقافي المنخفض والمشاكل العائلية هي أهم العوامل المؤهلة لسوء التغذية عند الأطفال . ولقد اختلفت الشكاوى والأعراض والتظاهرات السريرية والقيم المخبرية بين المرضى . تم تطبيق العلاج بمحلول F100 المعتمد من قبل منظمة الصحة العالمية في 19 حالة (تخرج 3 اطفال على مسؤولية الأهل, وتوفي طفل بعد ساعات قليلة من القبول) . ولقد أظهرت هذه المعالجة فعالية جيدة, حيث تم تقبله من قبل الأطفال المعالجين بشكل جيد, وزيادة الوزن الجيدة بمعدل (14.5 غ/كغ / اليوم) في المرحلة الثانية من العلاج, وكان معدل الإقامة في المشفى (10,4) يوم بالمقارنة مع( 9,29) يوم في دراسة د. محمود بوظو في مشفى دمشق (2001 ). راجع 16 طفلا من أصل 19 تلقوا العلاج بمحلول F100 بعد بضعة أشهر, وقد أظهروا تحسنا كبيرا من حيث زيادة الوزن, وغياب علامات عوز الفيتامينات, وتحسن الموجودات المخبرية. Our study – which was performed in Al-ASSAD university hospital in Lattakia from 10/2002 to 10/2003 – included 23 children suffering from severe malnutrition according to worldwide accepted Z-score, these children were admitted to the hospital for different reasons . They were distributed as: 15 have marasmus, 7 have marasmic kwashiorkor, 1 has kwashiorkor. Their age was between 40 days and 2 years, and they were 15 males, 8 females . We found in our study poverty, ignorance of the rules of correct pediatric nutrition, low cultural level ,and familial problems are the most important predisposing factors of malnutrition . The complaints, clinical symptomsand manifiestations, and laboratory findings have varied between patients . Treatment was applied by stages depending on (W H O) accepted F100 solution on 19 children (3 children were discharged on the resposibility of their parents, and one has died a few hours after admission to the hospital) the treatment showed good efficacy it was well accepted by children who were treated carefully, and good weight gain (14,5g\kg\day) in the second stage of therapy . The average of residency in the hospital was 10,4 days while it was 9,29 days in the study of Dr.M.Bodho in Damas hospital (2001) . 16 children of 19 (who received F100) were seen few months later and they showed great improvement, they had good weight, signs of malabsorbtion have disappeared, and their laboratory values were normal.